Determinants of Dual-task Gait Speed in Older Adults with and without Parkinson’s Disease - Ivaniski-Mello, André; Müller, Vivian Torres; de Liz Alves, Lucas; Casal, Marcela Zimmermann; Haas, Aline Nogueira; Correale, Luca; Kanitz, Ana Carolina; Martins, Valéria Feijó; Gonçalves, Andréa Kruger; Martinez, Flávia Gomes; Peyré-Tartaruga, Leonardo Alexandre (International Journal of Sports Medicine, 2023)
Mobility difficulties for people with Parkinson’s disease (PwPD) are more pronounced when they perform a simultaneous cognitive task while walking. Although it is known that neurodegeneration results in widespread motor and brain impairments, few studies have comprehensively examined possible physical and mental determinants of dual task walking in PwPD. In this cross-sectional study, we aimed to investigate if and how muscle strength (sit-to-stand 30-sec test), cognition (mini-mental state examination) and functionality (timed up and go test) affect walking performance (10-meter walking test) with and without arithmetic dual task from older adults with and without Parkinson’s disease. Walking speed was reduced by 16% and 11% with arithmetic dual task for PwPD (from 1.07±0.28 to 0.91±0.29 m.s−1, p<0.001) and older adults (from 1.32±0.28 to 1.16±0.26 m.s−1, p=0.002) compared to essential walking. The cognitive state was similar among the groups, but it was only associated with the dual-task walking speed in PwPD. In PwPD, lower limb strength was the better predictor of speed, whereas mobility was more related to it in older adults. Therefore, future exercise interventions aiming to improve walking in PwPD should consider these findings to maximize their effectiveness.
Keywords: locomotion; task performance; executive function; walking speed; multitasking behavior; physical fitness